Effect of Interference Electric Stimulation at Baliao and Dachangshu Acupoints Combined with Mosapride on Constipation Patients with Diabetes - JIANG Huiyu; ZHOU Wei; MING Xiaohong; LIU Haichao; WU Xiuxiang (康复学报)
ObjectiveTo observe the clinical effect of interference electric stimulation at Baliao and Dachangshu acupoints combined with mosapride on constipation patients with diabetes.MethodsA total of 40 constipation patients with diabetes in the outpatient department of the Second Affiliated Hospital of Hainan Medical College from January 2018 to December 2019 were randomly assigned to the control group and the observation group, with 20 cases in each group. The control group was treated with oral mosapride plus lifestyle intervention, and Mosapride was given orally five mg a time, three times a day, continuous treatment for two weeks. The observation group received interference electric stimulation at Baliao and Dachangshu acupoints on the basis of oral mosapride and lifestyle intervention. The frequency was (4 000±100) Hz, and the intensity was subject to the patient's tolerance, 20 minutes each time, once a day, continuous treatment for two weeks. Before and after treatment, the surface electromyography (EMG) of pelvic floor muscle was measured by multifunctional biological stimulation feedback instrument, the pelvic floor muscle strength was evaluated by Laycock score system, the quality of life of patients was evaluated by the MOS item short from health survey (SF-36), the constipation symptoms were evaluated by constipation symptom score scale, and the clinical effects of two groups were compared.ResultsThere was no significant difference in the scores of pelvic floor surface EMG, pelvic floor muscle strength and quality of life between the two groups before treatment (P>0.05). ① Pelvic floor electromyography: compared with that before treatment, the Pre baseline resting EMG and Post baseline resting EMG were decreased significantly (P<0.05), and the fast muscle systolic EMG, systolic EMG of synthetic muscle and slow muscle systolic EMG of two groups after the treatment were increased significantly (P<0.05); compared with the control group, the Pre baseline resting EMG and Post baseline resting EMG in the observation group after the treatment were decreased significantly (P<0.05), and the fast muscle systolic EMG, systolic EMG of synthetic muscle and slow muscle systolic EMG were increased significantly (P<0.05). ② Pelvic floor muscle strength: compared with that before treatment, the pelvic floor muscle strength of two groups after the treatment was increased significantly (P<0.05); compared with the control group, the pelvic floor muscle strength in the observation group after the treatment was increased significantly (P<0.05). ③ Clinical efficacy: compared with that before treatment, the scores of constipation symptoms such as defecation interval, stool characteristics, difficult/laborious defecation, incomplete defecation and anal/rectal obstruction were significantly reduced in the two groups (P<0.05); compared with the control group, the scores of constipation symptoms in the observation group after the treatment was reduced significantly (P<0.05). The clinical effect of the observation group was higher than that of the control group (P<0.05). ④ SF-36 score: compared with that before treatment, the quality of life score of two groups after the treatment was increased significantly (P<0.05); compared with the control group, the quality of life score in the observation group after the treatment was increased significantly (P<0.05).ConclusionInterference electric stimulation at Baliao acupoint and Dachangshu acupoint combined with mosapride can more effectively accelerate gastrointestinal peristalsis, relax anal sphincter and activate pelvic floor muscle, so as to promote defecation and improve defecation function.